The Use of Humor as a Pragmatic Device in Indonesian Studium Generale Lectures - Muhammad Rizqi (Balai Bahasa Kalimantan Tengah, 2020)
This paper concerns the use of humor as a pragmatic device in academic discourse. The previous studies in this area has shown that, though unlikely, humor is commonly used in academic discourse—both that of written and spoken nature. Among many aspects analyzed in the studies of academic discourse, some are related to academic cultures. With a deliberate consideration of this existing body of literature, this research aims to contribute in area by examining the use of humor in a specific academic environment, Indonesia. The data analyzed are selected transcripts from chosen YouTube videos of studium generale lectures by three Indonesian political figures. The usage of humor will be identified and analyzed pragmatically, and further classified on a table based on the classification of humor by Martin, Puhlik-Doris, Larsen, Gray, and Weir (2003). The findings of this study show that in Indonesian studium generale lectures, all four types of humor in the theory occurred, and the most frequently used type of humor is aggressive humor, to which offensive jokes belong.AbstrakArtikel ini membahas jenis dan fungsi humor dalam mata kuliah umum bahasa Indonesia. Ada beberapa aspek yang dianalisis dalam kuliah umum bahasa Indonesia yang dikaitkan dengan budaya akademik. Penelitian ini bertujuan untuk memerikan jenis dan fungsi humor dengan menelah penggunaan humor di lingkungan akademik di Indonesia. Data yang dianalisis adalah transkrip yang dipilih dari video YouTube yang dipilih dari kuliah umum oleh tiga tokoh politik Indonesia. Data diunduh terlebih dahulu lalu kalimat yang terkait dengan penelitian dicatat. Data yang terkait humor diidentifikasi dan dipilah sesuai dengan jenis dan fungsinya. Selanjutnya data diklasifikasikan berdasarkan klasifikasi humor oleh Martin, Puhlik-Doris, Larsen, Gray, dan Weir. Hasil penelitian menunjukkan bahwa terdapat empat jenis humor, yakni affiliative humor, self-enhacing humor, aggressive humor, dan self-defeating humor yang ada dalam kuliah umum di Indonesia. Yang paling sering digunakan adalah aggressive humor yang termasuk dalam lawakan ofensif.